CD146/MCAM defines functionality of human bone marrow stromal stem cell populations. Issue 1 (December 2016) - Harkness, Linda; Zaher, Walid; Ditzel, Nicholas; Isa, Adiba; Kassem, Moustapha
Abstract Background Identification of surface markers for prospective isolation of functionally homogenous populations of human skeletal (stromal, mesenchymal) stem cells (hMSCs) is highly relevant for cell therapy protocols. Thus, we examined the possible use of CD146 to subtype a heterogeneous hMSC population. Methods Using flow cytometry and cell sorting, we isolated two distinct hMSC-CD146+ and hMSC-CD146− cell populations from the telomerized human bone marrow-derived stromal cell line (hMSC-TERT). Cells were examined for differences in their size, shape and texture by using high-content analysis and additionally for their ability to differentiate toward osteogenesisin vitro and form bonein vivo, and their migrational abilityin vivo andin vitro was investigated. Results In vitro, the two cell populations exhibited similar growth rate and differentiation capacity to osteoblasts and adipocytes on the basis of gene expression and protein production of lineage-specific markers.In vivo, hMSC-CD146+ and hMSC-CD146− cells formed bone and bone marrow organ when implanted subcutaneously in immune-deficient mice. Bone was enriched in hMSC-CD146− cells (12.6 % versus 8.1 %) and bone marrow elements enriched in implants containing hMSC-CD146+ cells (0.5 % versus 0.05 %). hMSC-CD146+ cells exhibited greater chemotactic attraction in a transwell migration assay and, when injected intravenously into immune-deficient mice following closed femoral fracture, exhibited wider tissue distribution and significantly increased migration ability as demonstrated by bioluminescence imaging. Conclusion Our studies demonstrate that CD146 defines a subpopulation of hMSCs capable of bone formation andin vivo trans-endothelial migration and thus represents a population of hMSCs suitable for use in clinical protocols of bone tissue regeneration.